Aplikasi Metode Time Cost Trade Off Pada Proyek Konstruksi: Studi Kasus Proyek Pembangunan Gedung Indonesia - Mandiyo Priyo; Muhamad Raa’uf Aulia (Universitas Muhammadiyah Yogyakarta, 2015)
Time and cost are very infuential to the success and failure of a project. The measurement of project can be seen by the short time arrangment and minimum cost without denying the quality of project result. Systematically project management is very needed to make sure the time of project realization appropriate with the contract or it can be done faster so the cost will be able to be pressed. Moreover it is also to avoid paying the fine caused by the project lateness. The purpose of this research is to calculate the cost change and time project arrangment by adding work time variation and employed increment, then compare the result between fine cost and cost changing after the overtime and employee increment. Data in this research is secondary data from implementer contractor. Data analysis is used Microsoft Project 2007 program and time cost trade off method. The result from Microsoft Project 2007 program is critical path and result from time cost trade off method is duration velocity and increment cost in every activity that fasten. The result of this research indicated that (1) Time and cost optimum result of the adding work time (overtime) obtained at the age of project 242 days of work with total cost of project Rp. 10.481.732.644,58 with time efficiency project 24 days (9,02%) and cost efficiency project Rp. 43.019.556,39 (0,41%). (2) Time and cost optimum result of the employee increment obtained at the age of project 243 days of work with total cost project Rp. 10.482.934.084,43 with time efficiency project 23 days (8,65%) and cost efficiency project Rp. 41.818.116,54 (0,40%). (3) The best choise is with adding work time (overtime), because it produces time and cost efficiency highest with time efficiency project 24 days (9,02%) and cost efficiency project Rp. 43.019.556,39 (0,41%). (4) Cost expedite duration project (adding overtime or employee increment) cheaper than the cost that should be paid if the project failed and have to pay the fine.